Influence of Impregnation of Recycled Concrete Aggregate on the Selected Properties of Concrete - Jaskulski, Roman; Reiterman, Pavel; Kubissa, Wojciech; Yakymechko, Yaroslav (Materials (Basel, Switzerland), 2021)
The paper focuses on investigating the effect of impregnation of recycled concrete aggregate on the mechanical and durability properties of concrete using this aggregate. Cement paste, limewater and diluted water glass were used to impregnate the aggregate. Both a single impregnation and a double impregnation using two different solutions were carried out. A total of four groups of concrete series, with two values of w/c ratio (0.45 and 0.60), were made. Concrete made using the impregnated aggregate was tested and the results were compared with those of concrete made using untreated recycled aggregate of the same kind. The results indicate that impregnation of aggregate improves the mechanical properties of concrete in many cases but reduces its resistance to cyclic freezing and thawing. Furthermore, in the case of impregnation with two solutions, the order in which the impregnants are applied influences the effect obtained. Using the results received, the impregnation methods were ranked in order from best to worst. The best impregnation method proved to be with cement paste, followed by diluted water glass, while the worst results were obtained with limewater, followed by diluted water glass.
Keywords: impregnation; recycled concrete aggregate; freeze-thaw cycles; compressive strength; concrete durability